2018
DOI: 10.1002/mde.2997
|View full text |Cite
|
Sign up to set email alerts
|

Who's boss? Physiological measures during performance assessment

Abstract: Leadership in organizations consists of a complex process, which includes the interpersonal relationship with collaborators. By using a neuroscientific approach, we evaluated the effect of the presence of unidirectional versus reciprocal feedback (provided only by the leader or by both figures), as well as the assignment of a quantitative or just a qualitative assessment. Skin conductance level and response (SCL and SCR), as well as heart rate (HR), have been recorded during a role playing. Results revealed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
1
7
0
1
Order By: Relevance
“…Concerning autonomic measures, it was estimated that high levels of skin conductance level and heart rate would be found, especially in the different sorting tasks. High levels of these autonomic indices, in agreement with the literature, can be interpreted as cues of stress and emotional engagement [33,39], which may result from both the difficulty of having a clear representation of the different variables of priority, efficacy, and time attributable by the different goals as well as from awareness with respect to the need to complete the SAGT in the shortest RT.…”
Section: Introductionsupporting
confidence: 75%
“…Concerning autonomic measures, it was estimated that high levels of skin conductance level and heart rate would be found, especially in the different sorting tasks. High levels of these autonomic indices, in agreement with the literature, can be interpreted as cues of stress and emotional engagement [33,39], which may result from both the difficulty of having a clear representation of the different variables of priority, efficacy, and time attributable by the different goals as well as from awareness with respect to the need to complete the SAGT in the shortest RT.…”
Section: Introductionsupporting
confidence: 75%
“…Furthermore, hyperscanning paradigms are now able to obtain data on actions and social adaptation during human-to-human interaction (Balconi et al, 2019a , b ; Balconi and Fronda, 2020b ). If portability will be increased, co-bots could receive precious information about multiple and complex work–environment settings with multiple agents.…”
Section: Discussion: Neuroergonomics In the Organizationmentioning
confidence: 99%
“…They concluded that moral decision‐making consists of complex processes requiring leaders to evaluate the potential personal and social consequences of the decision to be made. In addition, innovative neuroscientific methods and paradigms that allow for study of two‐persons in interaction (“hyperscanning”) enabled researchers to underline the potential significant modulations of neurophysiological correlates in response to social challenges for different types of leadership styles (Balconi et al, 2019; Balconi, Venturella, Fronda, & Vanutelli, 2019).…”
Section: Methodologiesmentioning
confidence: 99%